Acceptance of students with disabilities in higher education institutions: a systematic literature review - Azmi, Nur Ain Nabisya; Wan Abdullah, Wan Arnidawati; Ashari, Asmidawati (Human Resource Management Academic Research Society, 2022)
This review focuses on the acceptance of students with disabilities in higher education. Due to the fact that peer acceptance or rejection can have a significant impact on the well-being of students with impairments, numerous relevant studies have been undertaken on attitudes toward these students. Unfortunately, the majority of previous studies focused on the effect of peer acceptance or rejection on the self-esteem, social skills, and inclusion of students with disabilities. Considering this, the present study conducted a comprehensive literature review on the factors that influence the acceptance of students with disabilities in higher education by students without disabilities. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) was utilised for the review of the current research, with Google Scholar, Scopus, and Taylor & Francis serving as the primary journal databases. The search efforts generated a total of 21 documents that can be thoroughly examined. The review was able to identify six major aspects of SWD acceptance: peer acceptance, disability closure, internalised disability acceptance, SWD acceptance, the relationship between knowledge and acceptance, and external support. Several suggestions for future researchers are provided at the conclusion of this study.